Primary Angiosarcoma of the Breast: A Rare Case Report in Postmenopausal Women - Issar, Pratibha; M., Ravindranath; Dewangan, Manish; Issar, Arnesh Kumar (Indian Journal of Radiology and Imaging, 2022)
Primary angiosarcoma (PAS) of the breast is a rare malignant tumor arising from endothelial cells lining the blood vessel and accounts for 0.04% of all breast tumors. It occurs predominantly in young patients usually presenting as nonspecific imaging features and is often overlooked and misdiagnosed at radiology and pathology. Angiosarcoma prognosis is generally poor; however, surgery followed by adjuvant chemotherapy and radiotherapy improves the prognosis. We report a rare case of PAS in a 65-year-old postmenopausal woman. She was diagnosed with PAS based on typical clinical, mammography, ultrasound, and magnetic resonance imaging (MRI) features followed by core biopsy of the lesion. Our case had the unique features of enlarged vessels within and surrounding the lesion in mammography, as well as in MRI, which could be very helpful for future diagnosis of this rare PAS in postmenopausal women.
Keywords: primary angiosarcoma; mammography; ultrasound; MRI